2018
DOI: 10.1186/s13037-018-0177-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of a two-screw cephalomedullary nail for intertrochanteric femur fracture fixation: a retrospective case series in 264 patients

Abstract: IntroductionRecent advances have led to the design of a new cephalomedullary nail, which aims to decrease the risk of failures in patients with intertrochanteric hip fractures by allowing for insertion of two interdigitating screws into the head segment. The goal of this study is to evaluate the safety and efficacy of this two-screw cephalomedullary nailing system.Patients/participantsPatients 18 years of age and older who underwent intramedullary nailing of their intertrochanteric femoral fracture using the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Both nail diameter groups were of adequate size to demonstrate any statistical difference present, and the follow-up period for these cases was long enough to cover the time frame in which mechanical failures are believed to occur most frequently. 13,14 Several of the findings in our study agreed with what is published in the contemporary orthopaedic literature regarding geriatric intertrochanteric femur fractures. Our patient cohort of all nail diameters had an average age of 77.5 with an overall reoperation rate of 8.3%, which is similar to all-cause reoperation rates reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Both nail diameter groups were of adequate size to demonstrate any statistical difference present, and the follow-up period for these cases was long enough to cover the time frame in which mechanical failures are believed to occur most frequently. 13,14 Several of the findings in our study agreed with what is published in the contemporary orthopaedic literature regarding geriatric intertrochanteric femur fractures. Our patient cohort of all nail diameters had an average age of 77.5 with an overall reoperation rate of 8.3%, which is similar to all-cause reoperation rates reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…The minimum follow-up of 12 weeks is adequate for detection of screw cutout and infection but may miss later complications of nonunion and periprosthetic fractures. 13,14 In judging reduction grades, there may be interobserver differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Femoral intertrochanteric fracture (FIF) is a fracture mostly associated with osteoporosis that occurs between the base of the femoral neck and the lesser trochanter and, as a common type of hip fracture in clinical practice, accounts for about 36% of hip fractures [ 1 , 2 ]. In recent years, with population aging, the incidence of FIF has also been increasing year by year and has become a serious traumatic disease threatening the health of the elderly [ 3 ], which greatly affects the short-term and long-term quality of life of patients [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deneca et al reported that basicervical femoral fractures have larger rotational instability than most other types [ 4 ]. Therefore, an improved cephalomedullary nail was introduced with two proximal screws including an antirotation screw with the purpose of increasing the rotational stability of the fracture, and excellent post-operative results with it were reported [ 5 , 6 ]. Recently, we encountered one basicervical femoral fracture case that caused a rare phenomenon; “reverse Z-effect”; after the surgery using a cephalomedullary nail with two superior antirotation screws.…”
Section: Introductionmentioning
confidence: 99%